Sistem Monitoring Kendaraan Dinas Secara Real-Time Dengan Menggunakan Metode Geo-fence Berbasis Android - Prima Dwiyana Nugraha; Derisma; Nefy Puteri Novani (CHIPSET, 2020)
This study aims to be a means in preventing the misuse of official vehicles. By using a geofencing system to monitor vehicles using Android. Because many government employees use official vehicles for personal use. In this system an application that has been installed with a geofencing system is installed on the smartphone. Then the system can track the gps of the vehicle you want to monitor. So that official vehicles can be monitored for their existence and the use of vehicles in a government agency can be used effectively and there is no misuse of state facilities.